Diabetes and Hypertension as Comorbidities Worsening Musculoskeletal Disorders in a Seamstress - Rusnianah, Farida; Nadya Syafitri, Wafa (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Musculoskeletal disorders like Frozen Shoulder (Adhesive Capsulitis) and Carpal Tunnel Syndrome (CTS) are common in the elderly, and their prognosis can be significantly worsened by the presence of uncontrolled chronic diseases and occupational risk factors. This case report highlights the complex interplay of these factors. This is a Family Medicine case report based on a holistic diagnosis approach. Data was collected through autoanamnesis, physical examination, and laboratory tests from a 61-year-old female patient. The assessment utilized the Family Genogram to identify genetic risk and the Family SCREEM to evaluate socioeconomic resources. The patient, a seamstress for over 40 years, presented with typical signs of Frozen Shoulder (limited Range of Motion, pain) and CTS (positive Tinel and Phalen tests). Her laboratory and physical findings showed uncontrolled chronic conditions, specifically a Random Blood Glucose of 311 mg/dL and Blood Pressure of 166/96 mmHg (HT Stage 2). Key risk factors identified were age (61 years), genetic predisposition (family history of DM and HT), and repetitive work activity combined with poor medication adherence. The conclusion is uncontrolled DM and HT are major risk factors contributing to the severity of musculoskeletal disorders in this patient. A patient-centered, family-focused, and community-oriented management plan is essential, involving strict pharmacotherapy adherence, lifestyle modification (ergonomics, exercise, diet), and ongoing family support to improve her functional status and prevent complications.